ANALISIS BIAYA PASIEN COVID-19 DI RUMAH SAKIT X KOTA BANJARMASIN - Aisyah, Noor Aisyah; Aisyah, Noor; Norhilaliyah, Norhilaliyah; Wahyuni, Amaliyah; Kumalasari, Eka; Yumassik, Abdul Mahmud; Illahi, Fitrah Shafran (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
COVID -19 is designated as an infectious disease that causes an outbreak and causes a public health emergency. COVID-19 causes death and absorbs significant disease costs. The research aims to determine the average cost of inpatient COVID-19 patients at hospitals in the city of Banjarmasin. This research is a descriptive non-experimental study using observational research methods, data was taken retrospectively to provide an overview of the costs of COVID-19 patients. The research sample is data on costs for inpatient COVID-19 patients in March-April 2020 at Hospital x Banjarmasin City with a sample size of 347 treatment episodes. The research results show that the average cost for a COVID-19 patient per episode of treatment is IDR 13,095,609. The total cost of all episodes of care for hospitalized COVID-19 patients is IDR 4,544,176,469. The first largest cost component that absorbs the most costs is the cost of drugs and medical materials amounting to IDR 1,236,714,000 per component with an average of IDR 3,564,017 per episode of care (27.215%). The second largest cost component is room costs, namely IDR 781,624,400 with an average cost of IDR 2,252,520 per treatment episode (17.20).